(untitled) (Journal of Information Systems and Technology Management, 2004)
The basic principle for design and handling of any Website in the Internet or Intranet is centered in the attractiveness, easy to manage, up-to-date, reliability and accuracy. When they are administered by a person and the information generated in different levels of the organization surpasses their capacity, we find places outdated, inexact and not very coherent that can tunnel the image and credibility of a company in the world of the Internet. Due to this problem arises the necessity of creating a tool that automates the creation process, approval and distribution of the information, guaranteeing its coherence and presentation, using a simple and concrete process, this way OBELISCO emerges, as a tool based on APIs open code with friendly and simple interfaces that allows users with little or no experience in technology to place its works in the Web.